LITERATUR REVIEW : TERAPI SPIRITUAL TERHADAP KUALITAS HIDUP PASIEN CHRONIC KIDNEY DISEASE (CKD) - Aprilianti, Fanizha Laila; Listyarini, Anita Dyah; Charista, Anindya; Safira, Anita Dila; Muniroh, Fitri Ambarwati; Muntiari, Lini (Jurnal Kesehatan dan Kedokteran, 2024)
Background : CKD is a late-stage kidney disease that can be caused by various things in which the body's ability fails to maintain metabolism and electrolyte fluid balance, which causes complications of hypertension and diabetes mellitus (Jainurrahma et al, 2021). The prevalence of chronic kidney failure in Indonesia has increased in 2018 to 0.38% or as many as 713,783 people based on a doctor's diagnosis in residents aged 15 years and over. Purpose: to find out the application of spiritual healing to the quality of life of Chronic Kidney Disease (CKD) patients. Method : research used by analyzing articles and searching through Google Scholar using the keywords "spiritual therapy and quality of life", "spiritual therapy and quality of life" + "chronic kidney disease",”spiritual therapy and quality of life" + "chronic kidney failure "management of spiritual healing and quality of life" + "chronic kidney disease”, “the effect of spiritual healing and quality of life”+ “chronic kidney disease” “psychological intervention and quality of life”+ “chronic kidney disease”. Results : from 9 journals it was found that spiritual healing can improve the quality of life in CKD patients. Conclusions : the application of spiritual healing to CKD patients undergoing hemodialysis therapy is able to improve the quality of life.